Polymeric Versus Lipid Nanoparticles: Comparative Study of Nanoparticulate Systems as Indomethacin Carriers - Carvalho, Ana; Lopes, Ivo; Gonçalves, Odete; Bárbara, Eduarda; Oliveira, M. Elisabete C.D. Real (Journal of Applied Solution Chemistry and Modeling, 2015)
Encapsulation of nonsteroidal or non-steroidal anti-inflammatory drugs (NSAID) in nanocarrier systems aims to enhance bioavailability and to decrease toxicity of these drugs and thus improve the efficacy of treatments. With this aim two types of nanoparticles were prepared and compared: lipid nanoparticles, made of cetyl palmitate and Miglyol 812 which were uncoated or coated with chitosan; or polymeric nanoparticles, made of poly (DL-lactic-co-glycolic acid) (PLGA) for which different emulsion stabilizers were also tested (poly (vinyl alcohol) (PVA), and Pluronic F68). Nanoparticles were characterized for drug content and for particle size, charge and morphology. The lipid matrix was analyzed regarding its crystallinity by differential scanning calorimetry (DSC). The size of the nanoparticles was measured by dynamic light scattering (DLS) which indicated a unimodal particle size distribution in all systems. Nanoparticles' stability was confirmed by their highly negative surface charge in the case of polymeric and uncoated lipid nanoparticles, as analyzed by zeta potential measurements using electrophoretic light scattering (ELS). Lipid chitosan coated nanoparticles have also shown to be stable presenting highly positive surface charge. Results have further demonstrated that indomethacin is highly encapsulated regardless the type of particles. Morphological analysis by scanning electron microscopy has shown that the nanoparticles were smooth and spherical. The results gathered within the current study point to the conclusion that the proposed formulations provide nanoparticles of satisfactory quality to encapsulate indomethacin, which might be used to improve bioavailability of other NSAID in the treatment of inflammation.